PERUBAHAN MINDSET KADER POS PAUD SEKAR MELATI JAYA TENTANG PENGENALAN CALISTUNG DI PAUD MENUJU PEMBELAJARAN BERORIENTASI BERMAIN - Kristanto .; Agus Suharno; Arri Handayani; Muniroh Munawar (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2015)
Abstract ?é?á The activities of devotion to the community it was implemented to cadres PAUD post in RW XX Meteseh village, Tembalang district, Semarang city to understand?é?á that?é?á :?é?á (1)?é?á of?é?á the?é?á importance?é?á of?é?á play?é?á as?é?á stimulation?é?á holistic?é?á early childhood; (2) Three types of play to learning oriented play in early childhood . This IbM is using a method of counseling and training. The counseling is about to give : (1) Technically the implementation of the PAUD post (2) Standard primary school curriculum grade 1. While training given to practice of three types of play in early childhood, that is:?é?á?é?á play sensorimotor area, play the role and play development. Mentoring also given as an application from the training practice of playing in PAUD post. The results of the implementation of activities IbM can be concluded that training oriented learning play introduce to cadres PAUD post about the types of play high quality in PAUD very useful in giving the image and equip cadre on the opening?é?á PAUD?é?á post?é?á Sekar?é?á Melati?é?á Jaya?é?á?é?á ?é?áRW?é?á XX?é?á Meteseh?é?á village,?é?á Tembalang district, Semarang city. Keyword: mindset, calistung, play